Dallas Mega Shelter Onsite Medical Operations Supporting Evacuee Functional Independence and Family Unit Integrity During Response to Hurricane Harvey. Issue Volume 34:Issue s1(2019) (May 2019) - Swienton, Raymond E.; Klein, Kelly R.; Liu, E. Liang; Flax, Lindsay A.; Fowler, Raymond L.
Abstract : Introduction: In the United States, over 50% of people have at least one chronic medical condition, access, or functional limitation. In 2017 during Hurricane Harvey, the establishment of a comprehensive multidisciplinary onsite medical clinic provided health and medical services to over 3, 800 evacuees at the Dallas Mega Shelter, providing large-scale general population sheltering support to all evacuees and prioritizing family unit integrity by meeting physical, sensory, and cognitive limitations, and chronic medical conditions. The effectiveness of the Dallas Mega Shelter onsite medical operations supporting this aim is reviewed. Aim: To utilize onsite health and medical resources to meet access and functional needs of evacuees seeking general population mass sheltering in Dallas, Texas during Hurricane Harvey. Methods: Observational. Results: Over 3, 800 evacuees were evaluated for functional needs support services (FNSS) resulting in over 2, 500 evacuee patient encounters during 21 continuous days of onsite health and medical clinic operations. 1 A comprehensive array of services were available at no cost to the evacuees and were in accordance with the Federal Emergency Management Association (FEMA) published Guidance on Planning for Integration of Functional Needs Support Service in General Population Shelters. 2 The goal to maintain nearly all evacuees choosing to stay in the Mega Shelter was achieved. The challenges, limitations, and risks identified are reviewed. Discussion: FNSS guidelines require all persons, regardless of limitations, when evacuated from home be provided all services necessary to allow them to remain in general population sheltering. 2 This prioritization of personal choice, functional independence, and family integrity for those with comprehensive FNSS requirements presented notable challenges, including public health and safety risks impacting the wellbeing of others. Meeting these expectations must be balanced with maintaining shelter integrity.